Digital Based Character Card Media to Improve the Character of Pancasila Students’ Profile in Elementary School - Rahayu, Suci; Harjito; Dini Rakhmawati (Journal of Education Reseach and Evaluation, 2025)
The issue of character development in Indonesia reflects the fact that character education has not yet been fully successful. This is due to various factors, including the influence of technological advancement, lack of supervision from parents and teachers, and the unavailability of effective media to support character formation. The aim of this study is to enhance the character traits of students as outlined in the Pancasila Student Profile through the development of an innovative, digital based character card media. The study employed the ADDIE development model. The research subjects included two media experts and two subject matter experts, while the product trial involved 49 students from classes VA and VIB. Data collection methods included observation, character survey tests, interviews, and questionnaires. The instruments used were questionnaire sheets and interview forms. Qualitative data analysis was applied in this study. The results showed that the average score given by media experts was 91%, indicating the media was "highly feasible." Content validation by subject matter experts yielded an average score of 92%, also categorized as "highly feasible." The normalized gain analysis for students' development of the Pancasila Student Profile produced an average N-gain score of 0.73, which falls into the "high" category. The Wilcoxon test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest groups. Therefore, it can be concluded that the use of digital-based character card media effectively enhances the character traits of elementary school students in alignment with the Pancasila Student Profile. The implications of the research are that digital based character card media is suitable for use in learning.